Komunikasi, Instagram, Parenting KONTEN EDUKASI PARENTING DI INSTAGRAM @POBEE.ID DALAM MENINGKATKAN PENJUALAN PRODUCT BERMAIN ANAK - Ardianto, Roni; Hastuti, Nurnawati Hindra; Astuti I, Andri (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
In the digital era like now, there are many applications that can be used as a field to make money, for example such as Instagram social media, which has now become an alternative media in the field of marketing and promotion. Broadly speaking, everyone can do business through Instagram social media. Instagram disseminates photos and videos with the features presented and the most popular social media. Pobee.id is present as a brand of children's toy manufacturers who use Instagram social media for buying and selling purposes to interact with followers. In addition to marketing purposes, what is interesting in this @pobee.id Instagram content is the method of educating how to use products and parenting packaged through videos (reels) and posting several images (carousel). The focus of this study is to find out how parenting educational content on Instagram pobee.id in increasing sales of children's play products. To explain the focus of this research in depth, this study uses qualitative research methods and interviews, in this study using theories from Hoghughi, Masud S, and Long (2004) Provide education and ensure that the education delivered by parents can run and can be carried out by children. The principle of parenting is more concerned with child development and activities related to education than with the child itself. From this study, it is revealed that parenting educational content can Pobee.id help informants in educating children to teach children activities that train stimulation so that it can reduce children's dependence on playing gadgets to be more creative and active. From the version, parents also get insight into how to educate children through play, and how the correct parenting style when children enter pre-school age can then be practiced at home when together with children. Through parenting educational content, pobee.id use it as a promotional medium on Instagram to sell children's play products, from data obtained by researchers every year pobee.id sales have increased, in the 2020 period product sales totaled Rp.70,176,419. for the 2021 period Rp.141,456,751. for the 2022 period Rp.176,472,842. for 2023, it was recorded that until November product sales had reached Rp.254,968,998. Keywords: Communication, Instagram, Parenting, Content Education